Comparative study on crack resistance of TiAlN monolithic and Ti/TiAlN multilayer coatings. Issue 5 (1st April 2020) - Shuai, Jintao; Zuo, Xiao; Wang, Zhenyu; Guo, Peng; Xu, Beibei; Zhou, Jia; Wang, Aiying; Ke, Peiling
Abstract: TiAlN monolithic and Ti/TiAlN multilayer coatings were fabricated on Ti–6Al–4V substrates by a self-designed multisource cathodic arc ion deposition system. The mechanical properties and crack evolution of the coatings were focused under scratch tests with different constant loads. Results showed that the multilayer coating exhibited a higher combination of plasticity, crack resistance and load capacity comparing to those of the monolithic coating. Namely, radical cracks, chippings, and lateral cracks were observed in the monolithic coating after scratch test, whereas only radical cracks occurred in the multilayer coating. The surface and cross-sectional morphology of the scratch tracks revealed that bending and shear stress were responsible for the failure of the two coatings. In particular, the ductile Ti layers within the multilayer coatings could coordinate the deformation and enhance the adhesion between the substrate and the brittle TiAlN layers, which further hindered the propagation of cracks, resulting in a higher crack resistance.